THE EMERGING DESIGN TRENDS OF HANDMADE EMBROIDERY ART IN PAKISTAN: A SOCIO-CULTURAL APPROACH - Maham Hafeez; Dr. Shafia Azam; Ms. Sidra Ashraf (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Handmade embroidery and needlework in Pakistan have indigenous significance with regard to its cultural heritage and aesthetic identity. The following research seeks to analyze the shift that has occurred in the practices and manifestations of embroidery designs in Pakistan. Handmade embroidery art and designs serve the purpose of aesthetic identity and the artistic ability for Pakistani women to develop their skills, additionally providing them autonomy and agency in the private and public realms of life. This ethnographic study was carried out to analyze the emerging embroidery art trends in relation to the altering patterns and practices of hand needlework in Pakistani society. The key data collection methods used in this study were participant observation and in-depth interviews. The study was conducted in the Rawalpindi neighborhood of Lalazar, Tulsa Road. Purposive sampling was used to collect data from 20 participants for in-depth interviews, including 10 hand embroiderers and 10 consumers from varied age groups, educational levels, and ethnic origins. The results suggest that patterns of embroidery making and its industry has gone through noticeable changes in the past decade but still, this form of art and design serves the purpose of identity, aesthetics and autonomy for women to develop their skills and take part in the economic prosperity. Additionally, the influence of media on the shifting trends in this field of art and design has been analyzed, and it has been concluded that social media platforms construct and promote the development of novel ideas and their dissemination into the world of fashion.